Variation in southern chinch bug (Blissus insularis) survival and damage on St. Augustinegrass germplasm. Issue 1 (29th April 2021) - van der Laat, Rocio; Dale, Adam G.; Arellano, Consuelo; Milla‐Lewis, Susana R.
Abstract: St. Augustinegrass [ Stenotaphrum secundatum (Walter) Kuntze] cultivars tend to be susceptible to the southern chinch bug ( Blissus insularis ; SCB). This insect feeds on the plant by sucking the sap, causing leaf chlorosis and necrosis, and can kill whole lawns. Resistant cultivars can simplify SCB management and reduce insecticide use. However, little research has been conducted to identify resistant germplasm that can be used in breeding. The objectives of this study were to (i) evaluate the level of damage caused by SCB feeding on sixteen St. Augustinegrass genotypes, and (ii) determine the attractiveness and quality of those genotypes to SCB in choice and no‐choice scenarios under greenhouse conditions. After a period of 6 wk of exposure in a choice study, SCB feeding damage on St. Augustinegrass [ S. secundatum (Walter) Kuntze] cultivars 'FX‐10', 'DALSA 0605' (TamStar ® ), 'SS‐100' (Palmetto ® ), and pembagrass [ Stenotaphrum dimidiatum (L.) Brongn.] accession PI 289729 ranged from 3 to 21%, demonstrating the highest resistance to SCB. Breeding lines XSA 10403, XSA 11168, and XSA 12354 suffered significant damage (>68%), indicating a high susceptibility to SCB. In a no‐choice study, '615866' (Seville ® ), 'SS‐100' and most breeding lines exhibited intermediate levels of SCB susceptibility, with SCB survival ranging from 35 to 74%. FX‐10, 'DALSA 0605', and PI 289729 were not suitable for SCB feeding and oviposition and exhibited two‐ to five‐fold reductions in the number of live SCB and eggs recovered per plant compared to most breeding lines. Several breeding lines proved to have higher levels of tolerance than cultivar 'Raleigh'. The magnitude of the differences between the most resistant and susceptible lines indicates that it is possible to generate biparental populations with enough segregation to conduct QTL mapping for SCB resistance. Core Ideas: Choice experiments identified genetic variation for levels of southern chinch bug damage No‐choice experiments identified genetic variation for southern chinch bug reproduction FX‐10, Dalsa 0605 ™ (TamStar ® ), and PI 289729 have high levels of resistance to SCB